1977
DOI: 10.2307/2060586
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breast feeding patterns on the biometric analysis of infant mortality

Abstract: A major assumption of the biometric analysis of infant mortality as developed by Bourgeois-Pichat is that the age structure of infant deaths after the first month of life is virtually constant across time and cultures. Reanalysis of results from studies which compare the mortality of infants according to the type of feeding indicated that the relationship between mortality and age within the first year of life followed different patterns for breast fed and artificially fed infants. Historical data for populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 13 publications
4
82
0
1
Order By: Relevance
“…In fact, it is impossible to reconstruct such information for historical European populations in a way that would allow for the construction of a database that would be useful for quantitative analysis. The only exceptions here are studies of breastfeeding habits, which usually show that early weaning leads to a sharp increase in infant mortality (Forste 1994;Knodel and Kintner 1977;Manda 1999;Rosenberg 1989). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it is impossible to reconstruct such information for historical European populations in a way that would allow for the construction of a database that would be useful for quantitative analysis. The only exceptions here are studies of breastfeeding habits, which usually show that early weaning leads to a sharp increase in infant mortality (Forste 1994;Knodel and Kintner 1977;Manda 1999;Rosenberg 1989). …”
Section: Discussionmentioning
confidence: 99%
“…Usually, many of the correlates are indirect measures or indicators of endogenous or exogenous causes. The most advanced studies of infant and child mortality rely on biometric variables such as birth weight, mother's nutritional status, and duration of breastfeeding (Knodel and Kintner 1977;Kuate-Defo 1997;Sear 2001). Such analyses provide a quite accurate picture of infant mortality since the aforementioned factors are the best predictors of mortality, especially during the early stages of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries, breastfed infants experience substantially lower Introduction 67 morbidity and mortality risks than infants who are not breastfed, particularly in the first year of life. [4][5][6][7][8][9] Breast milk is well known to have positive impact on child health. Research in public health has found that essential antibodies are present in the first breast milk (colostrum) and these antibodies provide the newborn with the needed protection against some infectious diseases and thus enhance the resistance to infectious disease attack.…”
mentioning
confidence: 99%
“…In order to gain greater insight into the nature and variation in breast-feeding practices in late nineteenth-century Belleville, we used the biométrie technique of Bourgeois-Pichat 98 coupled with the findings of Knodel and Kintner, 99 who applied this method on populations with known patterns of various feeding practices. In populations where breast-feeding was uncommon or short in duration, Knodel and Kintner found that infant mortality rises particularly steeply during the early months of the first year of life.…”
Section: 3mentioning
confidence: 99%